Stając się modlitwą. Trzy postaci, trzy głosy (tłum. B. Brzezińskiego) - Plekon, Michael (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article Becoming what we pray: Three images, three voices by professor Michael Plekon presents three persons who were very important for Orthodox culture, spirituality and thought — saint Seraphim of Sarov, Mother Maria Skobtsova and Paul Evdokimov. Showing the most substantial facts from their life and activity the author exhibits the real transformation, metamorphosis of their personalities, hearts and consciousnesses under the action of practice of the Jesus' Prayer or the prayer of the heart. The main aim of the article is — one can suppose — to underline the role of the Jesus' Prayer in changing people who systematically practicing it in their life, and in giving them the power to go over the stereotypes, myths and customs, even religious. The heart of the matter is emphasizing — in positive meaning — the real close union between the prayer andthe life and the relationship with neighbour. Professor Plekon stresses that “the personaland interior aspects of this prayer are never separated from liturgical prayer and ourlives”. Christians believe in salvation and resurrection of Jesus Christ and they practice the Jesus Prayer, but this prayer formula is not only devoid of life meaning formula but it is the method of changing the whole human mentality, in each everyday circumstances concerning family, marriage, work, life in monastic community, doing shopping, reading books, watching TV programs, raising children, writing the scientific articles, being in different social and cultural situations, generally — it changes all, the vision of life and the universe.